Glial Fibrillary Acidic Protein Autoimmunity: A French Cohort Study. (8th February 2022) - Gravier-Dumonceau, Alice; Ameli, Roxana; Rogemond, Veronique; Ruiz, Anne; Joubert, Bastien; Muñiz-Castrillo, Sergio; Vogrig, Alberto; Picard, Geraldine; Ambati, Aditya; Benaiteau, Marie; Rulquin, Florence; Ciron, Jonathan; et al.
Abstract : Background and Objectives: To report the clinical, biological, and imaging features and clinical course of a French cohort of patients with glial fibrillary acidic protein (GFAP) autoantibodies. Methods: We retrospectively included all patients who tested positive for GFAP antibodies in the CSF by immunohistochemistry and confirmed by cell-based assay using cells expressing human GFAPα since 2017 from 2 French referral centers. Results: We identified 46 patients with GFAP antibodies. Median age at onset was 43 years, and 65% were men. Infectious prodromal symptoms were found in 82%. Other autoimmune diseases were found in 22% of patients, and coexisting neural autoantibodies in 11%. Tumors were present in 24%, and T-cell dysfunction in 23%. The most frequent presentation was subacute meningoencephalitis (85%), with cerebellar dysfunction in 57% of cases. Other clinical presentations included myelitis (30%) and visual (35%) and peripheral nervous system involvement (24%). MRI showed perivascular radial enhancement in 32%, periventricular T2 hyperintensity in 41%, brainstem involvement in 31%, leptomeningeal enhancement in 26%, and reversible splenial lesions in 4 cases. A total of 33 of 40 patients had a monophasic course, associated with a good outcome at last follow-up (Rankin Score ≤2: 89%), despite a severe clinical presentation. Adult and pediatric features are similar. Thirty-two patients were treated with immunotherapy. A total of 11/22 patients showed negative conversion of GFAP antibodies. Discussion: GFAP autoimmunity is mainly associated with acute/subacute meningoencephalomyelitis with prodromal symptoms, for which tumors and T-cell dysfunction are frequent triggers. The majority of patients followed a monophasic course with a good outcome.